Sperm chromatin biological and clinical applications in male infertility and assisted reproduction - Zini, Armand; Agarwal, Ashok (Physician).; SpringerLink (Online service). (New York Springer, 2011)
Sperm DNA damage is common and has been associated with reduced rates of conception, impaired embryonic development and increased risk of miscarriage. Although the exact causes of sperm DNA damage are unknown, it is clear that infertile men possess substantially higher levels of sperm DNA damage than do fertile men. Written by leading, internationally renowned clinicians and basic scientists with expertise in sperm DNA, Sperm Chromatin: Biological and Clinical Applications in Male Infertility and Assisted Reproduction provides readers with a thoughtful and comprehensive review of the biologica.
Sperm Chromatin: An Overview -- Spermatogenesis: An Overview -- Sperm Nucleoproteins -- The Relationship Between Chromatin Structure and DNA Damage in Mammalian Spermatozoa -- Chromosome Positioning in Spermatozoa -- Sperm Mitochondrial DNA -- The Sperm Epigenome -- RNA Expression in Male Germ Cells During Spermatogenesis (Male Germ Cell Transcriptome) -- Sperm Chromatin Structure Assay (SCSAª): 30 Years of Experience with the SCSAª -- Sperm Chromatin Dispersion Test: Technical Aspects and Clinical Applications -- Basic and Clinical Aspects of Sperm Chromomycin A3 Assay -- Cytochemical Tests for Sperm Chromatin Maturity -- Acridine Orange Test for Assessment of Human Sperm DNA Integrity -- Laboratory Evaluation of Sperm Chromatin: TUNEL Assay -- Basic and Clinical Aspects of Sperm Comet Assay -- Assays Used in the Study of Sperm Nuclear Proteins -- Sperm Epigenetic Profile -- Clinical Significance of Sperm RNA -- Role of Oxidative Stress in the Etiology of Sperm DNA Damage -- Abortive Apoptosis and Sperm Chromatin Damage -- Spermiogenesis in Sperm Genetic Integrity -- Male Subfertility and Sperm Chromatin Damage -- Aging and Sperm DNA Damage -- Cancer in Males: Implications for Sperm Quality, Fertility, and Progeny Outcome -- Sperm Chromatin and Environmental Factors -- Effects of Male Accessory Gland Infection on Sperm Parameters -- The Impact of Sperm Processing and Cryopreservation on Sperm DNA Integrity -- Structure of Chromatin in Human Sperm Bound to Hyaluronic Acid: The Benefits of PICSI Dish Mediated Sperm Selection -- Electrophoretic Sperm Separation -- Antioxidants and Sperm DNA Damage -- Sperm Chromatin and ART (IUI, IVF and ICSI) Pregnancy -- Sperm DNA Damage and Pregnancy Loss After IVF/ICSI -- Postnatal Effects of Sperm Chromatin Damage -- Evaluation of Chromatin and DNA Integrity in Testicular Sperm -- Sperm Chromatin Structure Assay (SCSAª) -- Measurement of DNA Damage in Spermatozoa by TUNEL Assay -- Clinical Utility of Sperm DNA Integrity Tests.
Electronic reproduction.
Keywords: Spermatogenesis -- Genetic aspects; Infertility, Male -- Genetic aspects; Sex chromatin; Electronic books